A Simplified Method for Evaluating the Dynamic Response of the Metal Sandwich Structure under Explosion Load - Kun Liu; Hewei Liu; Yao Li; Zeping Wang; Jiaxia Wang (Metals, 2022)
The metal sandwich structure is characterized by light weight, high stiffness, and high-impact energy absorption capacity, which is considered a good alternative protective structure in explosion scenarios. In this paper, four design forms of the metal sandwich structure are introduced, and the dynamic response of the metal sandwich structure under explosion load is researched. Then, a new analytical method is proposed to predict the dynamic response of the metal sandwich structure under explosion load, and numerical simulations are carried out to verify the accuracy of the proposed analysis method. The proposed analytical method is designed for aerial explosions without considering the fluid–structure interaction. In addition, a series of parameter studies are carried out, including the influence of the face sheet aspect ratio, the core height, and the thickness of the face sheet and core on the dynamic response of the sandwich structure under explosion load. The research in this paper has reference value for the anti-explosion design of the metal sandwich structure and will provide a useful reference for the design and optimization of the metal sandwich structure.